ANALYSIS OF FACTORS AFFECTING THE COMPETENCY OF PHYSICS TEACHERS IN WEST SUMATRA PROVINCE - Hendri, Weria; Alias, Siti Nursaila; Daud, Anis Nazihah Mat; Halim, Anis Diyana (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Teachers’ competency plays a vital role in improving the quality of their teaching. Hence, this research was performed to analyse the factors affecting the Competency of Physics teachers in West Sumatra Province. This research employs a quantitative research design with a survey method. A total of 37 Physics teachers from junior and senior high schools in West Sumatra Province were selected as respondents of the research using the purposive sampling technique. A questionnaire was used as the primary instrument for this research. The finding indicated that most respondents agreed that a physics teacher's pedagogical, social, personality, and professional competencies in West Sumatra Province were significantly influenced by the self-concept (95%) and communication skills (100%). The respondents also suggested that Physics teachers should have digital literacy skills and support from school management to improve their competency level. The findings of this study can be used as a reference to develop the competency model of a Physics teacher in West Sumatra Province.